Limits of the Turkish Model Applicability in the Middle East Countries after the Arab Awakening: The Case of Egypt - D. V. Zhigulskaya (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Painful transformational processes taking place in the Middle East after the Arab Awakening pose not only new threats and challenges for regional actors, but also provide new opportunities for some of them to pursue their geopolitical ambitions and strengthen strategic positions, including through non-traditional methods and tools. In this regard, Turkey’s attempts to capitalize on the interest of some governments, which came to power on a wave of dissent, to learn from the Turkish experience in state building deserve independent consideration. These attempts were reflected in the concept of the so called Turkish model. In the early 2010s a particular interest in implementation of the Turkish model was shown by Egypt. The paper examines both the driving forces behind M. Mursi’s government special attention to Ankara’s example and the reasons that ultimately have led to the failure to operationalize the Turkish model in Egypt and the subsequent dramatic deterioration of bilateral relations. The first section of the paper identifies the key elements of the Turkish model. The author emphasizes that initially this model was aimed at identifying the optimal balance between religious and secular principles in public life. The second section explores M. Mursi’s government attempts to implement the Turkish model in Egypt in the first half of 2010s. The author shows that it was economic and political success of Turkey in the 1990s and 2000s including its rapid economic growth and the increase of foreign investments, as well as a successful inclusion of political Islam in the Western-style democratic institutions that primarily attracted the new Egyptian government. However, the author concludes that M. Mursi’s government failure to undertake profound economic, social and political reforms combined with a mixed attitude of the Muslim Brotherhood towards the Turkish model, growing popular discontent and a negative attitude of certain regional actors towards this proclaimed political course of the new Egyptian leaders have eventually led to the military coup and cessation of all attempts to learn from the Turkish experience. The third section outlines implications of the 2013 military coup in Egypt for the bilateral relations. The author concludes that the Egyptian case clearly demonstrates the limits of applicability of the Turkish model in the Middle East countries, as well as limitations of Turkey’s regional ambitions.